Rancang Bangun Aplikasi Audit Internal Fakultas (Studi Kasus: FMIPA Universitas Lampung) - Desrizal Dwi Ayu; Tristiyanto; Aristoteles (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Evaluation of faculty performance is an assessment of the quality of a faculty at the University. This Accreditation Assessment is carried out internally as well as externally by the National Accreditation Board for Higher Education (BAN PT). The Faculty of Mathematics and Natural Sciences is one of the faculties at the University of Lampung, where faculty accreditation is the most important educational support used as an assessment criterion, namely vision, mission, objectives, student archives, and others. The amount of data is one of the problems faced by faculties in storing accreditation data. Referring to the above problems, it is appropriate to develop an